Ni‐Co layered double hydroxide coated on microsphere nanocomposite of graphene oxide and single‐walled carbon nanohorns as supercapacitor electrode material. (5th September 2022) - Kim, Ji Hoon; Ko, Yong‐il; Lee, Seo Yun; Lee, Yun Seon; Kim, Su Kyung; Kim, Yoong Ahm; Yang, Cheol‐Min
Summary: Ni‐Co layered double hydroxides (LDH) have received considerable attention as excellent pseudocapacitor electrode materials. In this paper, a novel utilization of the composite of graphene oxide (GO) and single‐walled carbon nanohorns (SWCNHs) is reported as an effective substrate for LDH coatings. We successfully synthesized hierarchical nanostructures composed of Ni‐Co LDH as well as microsphere composites of GO and oxidized SWCNHs ( o ‐NH). A dense microsphere composite of GO and o ‐NH was synthesized using the spray‐drying method ( s ‐(GO/ o ‐NH)). Subsequently, the prepared Ni‐Co LDH nanosheets were directly coated on the s ‐(GO/ o ‐NH) microspheres using the hydrothermal method (LDH@ s ‐(GO/ o ‐NH)). Moreover, the electrochemical characteristics of the LDH@ s ‐(GO/ o ‐NH) supercapacitor electrodes were evaluated in a 6 M KOH electrolyte. In the three‐electrode system, the LDH@ s ‐(GO/ o ‐NH) composite electrode exhibited a significantly high gravimetric specific capacitance (1046 F g −1 at 1 mV s −1 ) and excellent specific capacitance retention (84% retention after 10 000 cycles at 100 mV s −1 ) compared with 211 F g −1 and 79% for the LDH@ s ‐GO composite electrode, respectively. The supercapacitive behavior of the LDH@ s ‐GO and LDH@ s ‐(GO/ o ‐NH) electrodes in the two‐electrode system exhibited a trend similar to that of the three‐electrode system. The superior electrochemical performance of the LDH@ s ‐(GO/ o ‐NH) composite electrode can be ascribed to its high electrical conductivity and pseudocapacitance, indicating that the s ‐(GO/ o ‐NH) microsphere composite with an interconnected pore network structure can be utilized as a support for effectively coating Ni‐Co LDH components. The LDH@ s ‐(GO/ o ‐NH) composite electrode is a promising candidate for pseudocapacitor applications because of its excellent electrochemical characteristics and facile synthesis, making it suitable for industrial and consumer applications. Abstract : Hierarchical composites composed of Ni‐Co layered double hydroxides (LDH) as well as microsphere composites of graphene oxide (GO) and oxidized single‐walled carbon nanohorns ( o ‐NH) were synthesized using spray‐drying and hydrothermal methods (LDH@ s ‐(GO/ o ‐NH)). The electrochemical characteristics of the LDH@ s ‐(GO/ o ‐NH) supercapacitor electrode were evaluated in a 6 M KOH electrolyte. The LDH@ s ‐(GO/ o ‐NH) composite electrode exhibited a significantly high gravimetric specific capacitance (1046 F g −1 at 1 mV s −1 ) and excellent specific capacitance retention (84% retention after 10 000 cycles at 100 mV s −1 ).